2022
DOI: 10.1093/mnras/stac105
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of bar formation in the Local Group

Abstract: More than 50 per cent of present-day massive disc galaxies show a rotating stellar bar. Their formation and dynamics have been widely studied both numerically and observationally. Although numerical simulations in the ΛCDM cosmological framework predict the formation of such stellar components, there seems to be a tension between theoretical and observational results. Simulated bars are typically larger in size and have slower pattern speed than observed ones. We study the formation and evolution of barred gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Analyses of galaxies in recent simulations of cosmological galaxy formation such as EAGLE and IllustrisTNG, etc. have also found that  ELN is incomplete to predict whether galaxies formed are barred or not (Yurin & Springel 2015;Algorry et al 2017;Izquierdo-Villalba et al 2022;Marioni et al 2022). A recent observational test based on statistically unbiased sample of barred/non-barred galaxies shows that the ELN criterion is largely inaccurate (Romeo et al 2023).…”
Section: Elnmentioning
confidence: 99%
“…Analyses of galaxies in recent simulations of cosmological galaxy formation such as EAGLE and IllustrisTNG, etc. have also found that  ELN is incomplete to predict whether galaxies formed are barred or not (Yurin & Springel 2015;Algorry et al 2017;Izquierdo-Villalba et al 2022;Marioni et al 2022). A recent observational test based on statistically unbiased sample of barred/non-barred galaxies shows that the ELN criterion is largely inaccurate (Romeo et al 2023).…”
Section: Elnmentioning
confidence: 99%
“…The constituent of each planet, the structure, and rotation model within the solar system are already investigated clearly. Some larger scale constructions in the universe, such as the Local Group [2], the Virgo supercluster [3] and the Laniakea supercluster [4], have been detected. As the intermediate object between star systems and these largest constructions, the Galaxy is a very necessary part of the research in this century.…”
Section: Comprehensive Purposementioning
confidence: 99%
“…9) with respect to the observed ones. More recently, the discrepancy between observations and simulations has been attenuated by the findings of Fragkoudi et al ( 2021 ) and Marioni et al ( 2022 ). Fragkoudi et al ( 2021 ) analysed the barred galaxies in the AURIGA simulation suite (Grand et al 2017 ) and showed that they have fast bars because they are more baryon-dominated with respect to those in the TNG simulation.…”
mentioning
confidence: 99%
“…Fragkoudi et al ( 2021 ) analysed the barred galaxies in the AURIGA simulation suite (Grand et al 2017 ) and showed that they have fast bars because they are more baryon-dominated with respect to those in the TNG simulation. Marioni et al ( 2022 ) investigated the evolution of barred galaxies in the CLUES simulation (Gottloeber, Hoffman & Yepes 2010 ), which have shorter, but not slower, bars with respect to their observed counterparts. A possible explanation for these findings could reside in the different ingredients of the simulations so far analysed, including the resolution of the simulation and the gas fraction, disc thickness, stellar and AGN feedback, and baryonic content of the simulated galaxies.…”
mentioning
confidence: 99%